2016
DOI: 10.3389/fendo.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Alters Lipid Storage in Diabetic Skeletal Muscle

Abstract: While statins significantly reduce cholesterol levels and thereby reduce the risk of cardiovascular disease, the development of myopathy with statin use is a significant clinical side effect. Recent guidelines recommend increasing inclusion criteria for statin treatment in diabetic individuals; however, the impact of statins on skeletal muscle health in those with diabetes (who already suffer from impairments in muscle health) is ill defined. Here, we investigate the effects of fluvastatin treatment on muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Given information gleaned from previous work as well as this investigation, it is hypothesized that Fluvastatin is inhibiting myoblast fusion in vitro via a mechanism independent of extracellular matrix remodeling. Although further investigation into this mechanism are warranted, the current investigation complements previous reports of the negative effects of statins on skeletal muscle health, which include changes in the adaptive response to stressors (current work), storage, and transport of lipids (Rebalka et al, 2016 ), and metabolic capacity/glucose handling (Ridker et al, 2008 ; Duvnjak and Blaslov, 2016 ).…”
Section: Discussionsupporting
confidence: 70%
“…Given information gleaned from previous work as well as this investigation, it is hypothesized that Fluvastatin is inhibiting myoblast fusion in vitro via a mechanism independent of extracellular matrix remodeling. Although further investigation into this mechanism are warranted, the current investigation complements previous reports of the negative effects of statins on skeletal muscle health, which include changes in the adaptive response to stressors (current work), storage, and transport of lipids (Rebalka et al, 2016 ), and metabolic capacity/glucose handling (Ridker et al, 2008 ; Duvnjak and Blaslov, 2016 ).…”
Section: Discussionsupporting
confidence: 70%
“…Muscle fiber cross-sectional area was calculated from Ն200 individual fibers per H & E-stained TA muscle section. The number of myopathic fibers was also quantified from H & E-stained TA sections as the sum of the number of centrally located nuclei per millimeter squared and the number of necrotic fibers per millimeter squared within the entire TA muscle cross-sectional area, as we have published previously (26). Muscle fiber types in TA cross-sections were determined by immunofluorescence using primary antibodies for myosin heavy chain I, IIa, and IIb (Developmental Studies Hybridoma Bank, University of Iowa), as described (2).…”
Section: Animal Protocols All Procedures Were Approved By the Mcmastermentioning
confidence: 99%
“…Muscle symptoms, such as fatigue, pain or weakness, are the most common statin side effects: these symptoms occur in up to 7% of statin users and up to 25% of statin users who participate in vigorous physical exercise [19]. Previous studies have shown that statin-induced muscle dysfunction is related to impaired mitochondrial function [2022], protein breakdown [23], reduced protein synthesis [24], decreased lipid uptake and synthesis [25] and increased ectopic lipid deposition [26]. Skeletal muscle accounts for the major glucose disposal site in the body, and impaired muscle viability or glucose uptake may result in a risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%